Do thrombolysis outcomes differ between anterior circulation stroke and posterior circulation stroke? A systematic review and meta-analysis. Issue 8 (October 2020) - Lee, Sang-Hun; Han, Jung Hoon; Jung, Ileok; Jung, Jin-Man
Background: It remains unclear whether thrombolysis outcomes can be influenced by the affected vascular territory (i.e. anterior circulation stroke vs. posterior circulation stroke) in stroke patients owing to the lack of randomized controlled trials. Aims: Using multiple comprehensive databases, we searched for observational studies of the safety and efficacy of intravenous thrombolytics and intra-arterial treatment with or without intravenous thrombolytics in accordance with the affected vascular territory. We performed a systematic review and meta-analysis. We evaluated symptomatic intracerebral hemorrhage, all-type intracerebral hemorrhage, mortality, and functional outcomes at three months. The recanalization rate was assessed in the intra-arterial treatment group. Summary of review: Twenty-one studies including a report from our own stroke registry were included through quantitative synthesis. Compared with the anterior circulation stroke group, the posterior circulation stroke group had a lower risk of ICH, including symptomatic intracerebral hemorrhage and all-type intracerebral hemorrhage, after intravenous thrombolytics and tended to have favorable functional outcomes at three months. Mortality was similar between the two groups. Regarding intra-arterial treatment, the symptomatic intracerebral hemorrhage and post-procedural recanalization rates were comparable between the two groups, although the posterior circulation stroke group had a higher mortality risk and lower tendency for a favorable functional outcome. Conclusions: Safety and efficacy of thrombolysis in posterior circulation stroke depends on involvement of large vessel occlusion and reperfusion modality such that intravenous thrombolytics is more effective and safer than in anterior circulation stroke; the safety and efficacy of intra-arterial treatment is comparable or lower than anterior circulation stroke. Considering the limitations of our meta-analysis, further studies are needed to provide high level evidence of a beneficial effect of intra-arterial treatment, and to identify patients' profiles associated with benefit of treatment.